2022
DOI: 10.7150/ijbs.66630
|View full text |Cite
|
Sign up to set email alerts
|

Icariside II enhances cisplatin-induced apoptosis by promoting endoplasmic reticulum stress signalling in non-small cell lung cancer cells

Abstract: Although cisplatin is the most effective first-line drug in the management of advanced non-small cell lung cancer (NSCLC), drug resistance remains a major clinical challenge. There is increasing evidence that icariside II (IS) exhibits antitumour activity in a variety of cancers. In the current study, we investigated the anticancer effects of icariside II combined with cisplatin and elucidated the underlying mechanism in NSCLC. Here, we showed that cotreatment with IS and cisplatin inhibited cell proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Therefore, many patients with cancer or autoimmune disease usually develop POF due to iatrogenic reasons. It is well-known that chemotherapy can induce cellular senescence [ 45 ] and apoptosis [ 46 , 47 ], and proliferative ovarian cells are more susceptible to chemotherapeutic drugs-induced damage than other quiescent cells [ 48 ]. Previous studies suggested that chemotherapy-induced cellular senescence and apoptosis in follicles and stromal cells, lead to decreased ovary weight, disrupted ovarian structure and atrophy, and alterations in hormone secretion and fertility [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many patients with cancer or autoimmune disease usually develop POF due to iatrogenic reasons. It is well-known that chemotherapy can induce cellular senescence [ 45 ] and apoptosis [ 46 , 47 ], and proliferative ovarian cells are more susceptible to chemotherapeutic drugs-induced damage than other quiescent cells [ 48 ]. Previous studies suggested that chemotherapy-induced cellular senescence and apoptosis in follicles and stromal cells, lead to decreased ovary weight, disrupted ovarian structure and atrophy, and alterations in hormone secretion and fertility [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that the ER stress response pathway plays an important role in cancer initiation and progression, and the therapeutic efficacy of cancer can be improved by modulating the ER stress process. For example, Icariside II can partially enhance cisplatin-induced apoptosis by promoting ER stress signalling in NSCLC[ 21 ]. There are also some researches suggesting that Chalcomoracin can increase the sensitivity of lung cancer cells to radiotherapy by enhancing endoplasmic reticulum stress[ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…IS was reported as a potential anti-in ammatory drug for a series of in ammatory diseases such as atherosclerosis, Alzheimer's disease, depression, osteoarthritis, and asthma (23). Moreover, a recent study demonstrated that IS could potentiate cisplatin-induced apoptosis in non-small cell lung cancer cells (8), overcome TRAIL resistance of melanoma cells (7), and enhance paclitaxel-induced apoptosis in human melanoma A375 cells. Thus, we infer that IS might be a promising agent for patients with NSCLC and COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies demonstrated that IS could enhance the anti-tumor effect of the mainstream medication including paclitaxel (6), TRAIL (7), and cisplatin (8). In addition, COVID-19 was considered with cytokine storm syndromes and immunosuppression (9).…”
Section: Introductionmentioning
confidence: 99%